Plant communities in urban habitats of Istanbul-Turkey - (:unkn) unknown (My University, 2012)
This study aims to analyze and classify distribution of urban vegetation as plant communities in Anatolian Side of Istanbul Turkey. The study was carried out in all districts of the Anatolian side excluding Şile and in total, 223 quadrates were recorded during 2004-2009 vegetation periods. Braun-Blanquet method was used for classification. As a result of the study, a total of 13 plant communities distributed in the study area was found. The plant groups were; Sarcopoterium spinosum, Erica manipuliflora, Tordylium apulum, Sinapis arvensis, Rapistrum rugosum, Carduus pycnocephalus, Carduus nutans, Centaurea iberica, Centaurea solstitialis subsp. solstitialis, Rumex crispus, Ammi visnaga, Cichorium intybus and Parietaria judaica. The floristic, ecologic and syntaxonomic analyses of these plant groups were realized and their distributions in the study area were given. Additionally, some soil properties such as maximum water holding capacity, pH, electrical conductivity, organic matter, CaCO3, P2O5, K2O and texture (sand, silt and clay) were analyzed. The formation and development conditions of them were described and discussed at the end of the paper. Protection against damage of this vegetation or at least protection of the existent situation was presented as suggestions.